The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3329/bjvm.v16i1.37368
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotics and Phytoextracts on Growth and Immunomodulating Performances of Broiler Chickens

Abstract: An investigation was carried out to find out the effects of probiotics and phytoextracts (Korolla-bitter melon, Triphalatraditional three herbal components and Safi-commercial polyherbal products) on growth, hemato-biochemical (TEC, TLC, ESR, Hb concentration, PCV, ALT, AST, Cholesterol, Tryglyceride, HDL and LDL) and immunomodulating performance of broiler chickens. The study was performed from February to April, 2017. A total of 150, seven -days-old broiler chicks were divided into five (05) groups using 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…There was non-significant difference in serum alanine aminotransferase concentration of broiler chicks in all groups up to 15 th and 30 th day of experiment. These results are in accordance to the results reported by Abdel-Fattah et al (2008), that supplementation of probiotics did not cause alterations in the ALT level, which proves that it is safer option for the liver, and it has been endorsed by Zuhra et al (2018). At the 42 nd day of experiment, there was a significant increase in serum alanine aminotransferase concentration of broiler chicks in infected groups B2, C2 and C2 compared to other groups and it is accordance to the results reported by Schimidt et al (2007), This change in ALT level can be attributed the tissue damage induced by the NDV in the birds.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…There was non-significant difference in serum alanine aminotransferase concentration of broiler chicks in all groups up to 15 th and 30 th day of experiment. These results are in accordance to the results reported by Abdel-Fattah et al (2008), that supplementation of probiotics did not cause alterations in the ALT level, which proves that it is safer option for the liver, and it has been endorsed by Zuhra et al (2018). At the 42 nd day of experiment, there was a significant increase in serum alanine aminotransferase concentration of broiler chicks in infected groups B2, C2 and C2 compared to other groups and it is accordance to the results reported by Schimidt et al (2007), This change in ALT level can be attributed the tissue damage induced by the NDV in the birds.…”
Section: Discussionsupporting
confidence: 92%
“…From 6 th week of age, Hb concentration was significantly lower in infected groups B2, D2, and E as compared to control group A. Seyidoglu et al (2013) and Zuhra et al (2018) reported that Hb concentrations were increased by supplementation of yeast, phyto-substances and probiotics in feed.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Shahadat et al [7] reported that, besides its anthelmintic effect, MC extract (30 g/liter drinking water) provides live weight gain in chickens infected with Ascaridia galli. Likewise, it has been reported that extract of MC improved the body weight of broiler chickens as feed additives, reduced liver function enzymes, and changed the lipid profile [12]. Nevertheless, comprehensive studies on the effect of MC on poultry performance are not enough.…”
Section: Introductionmentioning
confidence: 99%